PEMODELAN DAN IMPLEMENTASI DESAIN RESPONSIVE WEBSITE SEBAGAI STANDAR INTERFACE PADA MOBILE - Anugerah Bagus Wijaya; Irfan Santiko (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
The development of digital technology in this period is very high. The need for consumption of information is so strong that it causes the growth of devices or media to obtain information varies. From the start of print media to electronic media, it is also increasingly prevalent. From observing the development of electronic media, various kinds of devices or can be called "Mobile" have undergone increasingly rapid reduction, ranging from personal computers to devices such as smartphones, tablet PCs and so on to become more concise. In short, in the media there are various supporting applications to provide information such as websites, for example. The more concise the tool used, the shorter the design that is presented in the application. In this study, we will review the analysis and suggestions for web design that are used to be more flexible and responsive to all the hardware used by the community in general.